Pengaruh Financial Knowledge, Attitude terhadap Behavior Pengguna E-wallet Pelaku UMKM Madura - Intan Fajar Daratista; Arie Setyo Dwi Purnomo; Prasetyo Nugroho (Komunitas Dosen Indonesia, 2024)
This study seeks to research the effect of financial knowledge and financial attitude on financial behaviour among e-wallet users in MSMEs in Madura. A quantitative approach was used, with data collected from 100 respondents through Google Form questionnaires using a Likert scale of 1–5. Instrument validity and reliability tests were carried out to guarantee data accuracy, and classical assumption tests including normality, multicollinearity, and heteroscedasticity were applied to meet regression requirements. The F-test results imply that financial knowledge and financial attitude have a significant and simultaneous impact on financial behaviour. A coefficient of determination (R²) of 30.7% demonstrates that these variables explain part of the variation in financial behaviour, implying that 30.7% of financial behaviour among MSME e-wallet users can be related to financial knowledge and attitude. The remaining 69.3% is impacted by various factors external to the model, suggesting that additional variables may play a crucial role. The findings confirm that financial knowledge and financial attitude substantially shape financial behaviour among e-wallet users in MSMEs in Pamekasan, Madura, underscoring their importance in financial behaviour improvement efforts within this context.